Structural, optical, and physical properties of GeOշ-PbO-BiշO³ glass - Poor Farkoosh, Hamid-Reza Bahari (2012)
The lead bismuth germanate glasses are of growing interest, due to their low cut-off optical phonon energy, high linear and nonlinear refractive index and excellent infrared transmission. Fabrication of metallic nanostructures embedded in glass matrix also attracts many researchers because of their enhancement ability of photoluminescence and optical nonlinearity. However, fabrication of metallic nanostructure other than sphere in glass matrix still is a challenge where met with a very limited success. To achieve the research objectives, the undoped and Er3+/Yb3+ doped germanate based glasses samples were prepared. This thesis reports the preparation of GeO2-PbO-Bi2O3 ternary glass system with and without Er3+/Yb3+ by melt cast-quenching method. All samples are studied by a wide range of characterization techniques which includes their structure, elastic and optical properties. An attempt has been made to add silver nanostructures into the germanate based glasses by thermal reduction of melt-quenched glass in order to study the formation of nanostructures in the vitreous network. In the germanate based glasses system the bismuth atom will be substituted by the lead atom to achieve almost mass independent properties due to their closeness of atomic masses. Structure and physical properties were studied by X-ray diffraction,Fourier transform infra-red (FTIR), density, ultrasonic velocities, UV-Visible absorption, photoluminescence and transmission electron microscopy (TEM). All of the samples were fully amorphous and their density, ultrasonic velocities and elastic moduli are relatively low for high lead content samples. FTIR peaks related to PbO covalent bond and bending Bi-O bond of BiO6 group which are formed when both Pb and Bi act the role of former in glass network, were observed in high lead content samples in contrast with low lead samples. The FTIR data also showed that germanium participated in glass structure with both of four-fold and six-fold coordination in all of samples. The UV-visible absorption of the glasses studied showed highest energy of band-gap for Pb-rich samples and also showed characteristic peaks of Er3+/Yb3+ ions. The photoluminescence spectrum obtained by excitation at wavelengths of highest absorption peaks, showed highest intensities for samples with highest lead content which related to lowest non-radiative relaxation in Pb-rich samples. The GeO2-PbO glass dopped with Er2O3, Yb2O3 and AgNO3 were also prepared by melt quenching method. Annealing of the glass were utilized for thermally reducing of Ag+ ions to metallic silver. The TEM results showed that the annealing process at 450˚C caused the formation of silver nanoparticles of about 3 nm mean diameter size. The samples which were annealed at 400˚C temperature showed the formation of silver nanoplates with mean length size of 60 nm embedded in glass matrix. The UV-Visible absorption also confirmed the existence of metallic silver nanostructure. The FTIR shows peaks at 470 cm-1 for 450˚C annealed samples, in contrast with 400˚C annealed samples, which suggest the existence of Pb-O chains in the germanate glass network. This is the main source of difference in formation of various nano structures due to different stabilizing medium and better physical isolation of glass matrix in 450˚C annealed samples.